PERBANDINGAN KARAKTERISTIK PENCAIRAN BATUBARA BANKO DAN YALLOURN SEBAGAI EFEK DARI PERUBAHAN SUPLAI HIDROGEN - Yuli Artanto; Yusnitati Yusnitati (Jurnal Energi dan Lingkungan (Enerlink), 2008)
A comparison of liquefaction characteristic of two brown coals (South Banko andYallourn coals) was studied. A 5L autoclave batch reactor was used under thecondition with temperature at 450 oC , reaction holding time 60 minutes. Theinitial hydrogen pressure was varied to compare the effect of different reactionpressure on the product perolehans. The oil yield for Banko Selatan and Yallournincreased 6% and 18%, respectively, by increasing initial hydrogen pressurefrom 10 MPa to 15 MPa. However in accordance with increasing pressure from15 MPa to 20 MPa, the yield did not change remarkably. On the other hand, theCLB perolehan was significantly decreased for both coals when the pressure wasincreased from 10 to 15MPa. Moreover, the CLB yield was abruptly decreasedwhen the hydrogen pressure drastically change to 20Mpa. It was found that theincreasing reaction pressure only affected to the yield of hydrocarbon gas slightlybut remarkably influenced the CO and CO2 gas production for Yallourn coal butnot for South Banko coal.Kata Kunci: coal liquefaction, south banko coal, yallourn coal, oil yield